2019
DOI: 10.1002/cam4.2565
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes for ibrutinib in relapsed or refractory mantle cell lymphoma in real‐world experience

Abstract: Ibrutinib is highly effective in patients with relapsed or refractory mantle cell lymphoma (MCL) in major clinical trials. Although there has been a dramatic improvement in survival outcomes in the salvage setting, nonresponders to ibrutinib have a bleak prognosis. Therefore, this retrospective study was conducted to identify the most appropriate therapeutic strategy and prognosis‐related factors to predict the response of patients with relapsed or refractory MCL to ibrutinib monotherapy. Thirty‐three consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 26 publications
5
35
3
Order By: Relevance
“…ORR was 93.8%, with CR seen in 31.3% of patients by the end of the phase II follow-up [78]. Real-world data of ibrutinib monotherapy in a salvage setting in Korea showed a favorable ORR and duration of response; however, higher MIPI and/or prior bendamustine exposure was associated with ibrutinib treatment failure and poorer outcomes [79]. Additional data from a Korean retrospective analysis of 75 patients with advanced MCL treated with ibrutinib reported a 70% ORR; at a median follow-up of 30.5 months, the median PFS was 18.6 months; and among elderly patients, better outcomes from ibrutinib were achieved in second-line versus later lines of therapy (median PFS 24.4 versus 5.8 months; P = 0.015) [80].…”
Section: Relapsed/refractory Diseasementioning
confidence: 95%
“…ORR was 93.8%, with CR seen in 31.3% of patients by the end of the phase II follow-up [78]. Real-world data of ibrutinib monotherapy in a salvage setting in Korea showed a favorable ORR and duration of response; however, higher MIPI and/or prior bendamustine exposure was associated with ibrutinib treatment failure and poorer outcomes [79]. Additional data from a Korean retrospective analysis of 75 patients with advanced MCL treated with ibrutinib reported a 70% ORR; at a median follow-up of 30.5 months, the median PFS was 18.6 months; and among elderly patients, better outcomes from ibrutinib were achieved in second-line versus later lines of therapy (median PFS 24.4 versus 5.8 months; P = 0.015) [80].…”
Section: Relapsed/refractory Diseasementioning
confidence: 95%
“…Ibrutinib is indicated for CLL as well as for many B-cell lymphomas [26][27][28][29] [30]. In other studies, the ORR was 48.0% in patients with MZL, 37.5% in patients with FL, and 90.0% in patients with WM [28,31,32].…”
Section: Resultsmentioning
confidence: 96%
“…Unlike ibrutinib monotherapy in CLL/SLL, it might not be enough for patients with MCL. A real-world study indicated a median OS and PFS after ibrutinib monotherapy in R/R MCL patients were 35.1 months and 27.4 months, respectively [21]. This might be interpreted by the biological differences and more complex cross-action signaling pathways in MCL patients.…”
Section: Ibrutinib Monotherapy In MCLmentioning
confidence: 99%
“…This might be interpreted by the biological differences and more complex cross-action signaling pathways in MCL patients. Therefore, ibrutinib monotherapy might not be the best choice for this population and other choices such as combination strategies followed by stem cell transplantation might be favorable for them [21].…”
Section: Ibrutinib Monotherapy In MCLmentioning
confidence: 99%